2010
DOI: 10.1016/j.jus.2009.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional sonohysterography for examination of the uterine cavity in women with abnormal uterine bleeding: Preliminary findings

Abstract: KEYWORDSSonohysterography; Three-dimensional sonohysterography; Hysteroscopy; Abnormal uterine bleeding.Abstract Introduction: To compare the diagnostic values of three-dimensional sonohysterography (3DSH), transvaginal ultrasound (TVUS), and 2-dimensional sonohysterography (2DSH) in the work-up of abnormal uterine bleeding (AUB), in particular the ability of each method to identify intracavitary lesions arising from the endometrium or uterine wall. Materials and methods: 24 patients referred for AUB underwent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…The high accuracy of 2D sonohysterography with intracavitary lesions -mainly polyps and submucous fibroids -is supported by several studies [5,11,[13][14][15][16][17]. Table 4 summarizes a comparison of our present results with those of formerly mentioned studies.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The high accuracy of 2D sonohysterography with intracavitary lesions -mainly polyps and submucous fibroids -is supported by several studies [5,11,[13][14][15][16][17]. Table 4 summarizes a comparison of our present results with those of formerly mentioned studies.…”
Section: Discussionsupporting
confidence: 81%
“…Several studies have previously demonstrated that 3D-SIS has an accuracy approaching 100% in the detection of intrauterine polyps and fibroids [14,17,19,22,23]. A comparison of Hysteroscopy showing an endometrial polyp.…”
Section: Discussionmentioning
confidence: 99%
“…Sconfienza et al (21) studied Three-dimensional sonohysterography for examination of the uterine cavity in women with abnormal uterine bleeding and found that 3D sonohysterography has 100% sensitivity, specificity, PPV, NPV and accuracy when compared to hysteroscopy as the gold standard.…”
Section: Discussionmentioning
confidence: 99%
“…Hysteroscopy in combination with histopathology is the gold standard for diagnosis and treatment of endometrial polyps [16][17][18][19]. Although invasive methods are very helpful in finding the possible causes of abnormal uterine bleeding, they can sometimes be expensive and uncomfortable [20,21]. Noninvasive methods are applicable to diagnose abnormal uterine bleeding before or after menopause and enable the individual to determine which invasive procedure (e.g.…”
Section: Introductionmentioning
confidence: 99%